INNOVATIVE METHODS OF TEACHING ENGLISH AND OTHER LANGUAGES IN HIGHER EDUCATION (Proceedings of International Educators Conference, 2023)
Currently, a huge base of experience that a teacher can use during his career has been formed, and it is getting richer every day. But nevertheless, it is difficult for teachers and future professionals to master these experiences. The role of the teacher in creating best practices and popularizing them among colleagues is of special importance. Educators should consider the cost and effectiveness of new pedagogical practices. The orientation of the teacher's practical activity to innovation allows the practical application of the achievements achieved as a result of theoretical pedagogical research.